Monitoring of fault level in future grid scenarios with high penetration of power electronics‐based renewable generation - Rafat Aljarrah; Hesamoddin Marzooghi; James Yu; Vladimir Terzija (IET Generation, Transmission & Distribution, 2021)
Abstract This paper proposes a novel method for quantifying fault level in future grid scenarios with various penetrations of power electronics‐connected renewable energy sources. As it is known, the information regarding the fault level is critically important for designing protection schemes, different control loops, understanding voltage profile in the grid, etc. This method is focused on the steady‐state fault level calculation and it can be used to analyse future grid scenarios including uniform and non‐uniform penetration of power electronics‐based generation displacing all, or just specific conventional synchronous generation in the grid. Due to different possibilities for type, size, and location of power electronics‐based RES generation in future grid, it is required to analyse the unprecedented scale of scenarios. The proposed method for FLC enables us to assess the system fault level for large numbers of FG scenarios without a need for detailed system modelling and/or time‐domain simulations. The simulation results demonstrated the suitability of our proposed FLC method for various penetration levels of PE‐based RESs in the 2‐area and the IEEE 39‐bus test systems. The obtained results are compared with time‐domain simulations and the IEC 60909 standards performed in DIgSILENT PowerFactory, where the efficacy of the proposed methodology is demonstrated.